Faktor-Faktor Yang Berhubungan Dengan Gejala Dermatitis Kontak Iritan Pada Pekerja Bengkel Motor Formal Di Kecamatan Pancoran Mas Kota Depok Tahun 2021 - Wardah Salsabillah; Cornelis Novianus; Trimawartinah Trimawartinah (Jurnal Keselamatan, Kesehatan Kerja dan Lingkungan, 2022)
Irritant contact dermatitis is contact dermatitis caused by irritant substances that can cause tissue damage and clinical abnormalities in the form of polyformic fluorescence (edema, papules, erythema, vesicles, scales, lichenification) and complaints of itching. The aim is to determine the factors associated with the occurrence of irritant contact dermatitis in formal motorbike repair workers in Pancoran Mas Sub-district, Depok City 2021. This study uses a quantitative cross-sectional study design. Samples were taken as many as 60 respondents with total sampling technique. The data used in this study is primary data by collecting data using questionnaires through interviews and examinations with doctors. The data analysis used in this study was univariate and bivariate analysis using the Chi-Square Test. The results of this study showed that there was a relationship between years of service (0.002), length of contact (0.029), personal hygiene (0.017), history of skin disease (0.001), use of PPE (0.025) with symptoms of irritant contact dermatitis.